1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

# prove that- i)cos?cosec?-sin?sec?/cos?+sin?=cosec?-sec? ii)cot^2?(sec?-1)/(1+sin?)=sec^2?(1-sin?)/(1+sec?) iii)(1-cos?)^1/2/(1+cos?)^1/2=sin?/1+cos? iv)(1+sin?)^1/2/(1-sin?)^1/2=cos?/1-sin?

Asked by Aditya Chakravarty 15th September 2013, 4:26 PM
Please ask one question at a time. The solution to your first question is as follows:

L.H.S.

= cos A . cosec A - sin A . sec A / cos A + sin A

= [(1 / sec A) . cosec A - (1 / cosec A) . sec A ] / [(1 / sec A) + (1 / cosec A) ]

= [cosec A / sec A - sec A / cosec A ] / [ cosec A + sec A / sec A . cosec A ]

= [cosec2 A - sec2 A / sec A . cosec A ] / [ cosec A + sec A / sec A . cosec A ]

= (cosec2 A - sec2 A) (sec A . cosec A) / sec A . cosec A (sec A + cosec A)

= (cosec A - sec A) (cosec A + sec A) / (sec A + cosec A)

= cosec A - sec A

= R.H.S.

Answered by Expert 15th September 2013, 10:13 PM
• 1
• 2
• 3
• 4
• 5
• 6
• 7
• 8
• 9
• 10

You have rated this answer /10